Educational Issues in the Learning Age - Edited by Matheson, Catherine and Matheson, David (London Continuum, 2000)
Education and its context are both changing rapidly. In a world characterized by postmodernism and globalization, even the discourses that we use to discuss education are changing. This raises fundamental questions concerning the relationship of education to culture, identity, society, and power. To understand education in the twenty-first century we need a new map. By considering issues both fundamental and tpoical from citizenship to lifelong learning, from school effectiveness to learning outside the school, this book provides a comprehensive, multi-disciplinary guide to education in the new.
Include Index
Keywords: Education--Philosophy -- Education--Social Aspects -- Continuing Education